Strontium, Arsenic and Arsenic species in beverages from the Portuguese Total Diet Study - Coelho, Inês (2016)
The main objective of this study was to study the levels of strontium, total arsenic and inorganic arsenic present in nectars, fruit juices and waters consumed in Portugal. A second objective was to evaluate the reliability of pooled versus single samples to derive consistent estimates of exposure assessment to inorganic contaminants. Twenty four samples of juices and nectars representative of the domestic market were acquired in May 2014 in the Lisbon region. Samples of representative brands were collected randomly in supermarkets of national implementation in accordance with consumer preference. Afterwards these were analyzed both as single units and as two pools, one of nectars and the other of juices, composed by 12 samples each. Prior to analysis samples were digested by high pressure closed vessel microwave digestion using only ultrapure reagents. An ICP-MS was used to quantify the levels of Strontium and Arsenic present in samples. Whenever the concentration obtained for arsenic was equal or above 5 µg.l-1 samples were signalized for speciation studies. These were carried out by coupling an HPLC to the ICP-MS, and enabled the determination of two inorganic arsenic species, As(III) and As(V), as well as two other organic species, AsB and DMA. Extraction of arsenic from samples was based on previously published work [1] and consisted on a dilution and a filtration steps previously to introducing the samples to the HPLC. Arsenic was found above the LQ (LQ=2 µg.l-1) in almost half the samples under study which shows that arsenic speciation is crucial to clarify the toxicity of arsenic present in foodstuffs. The speciation study proved that most of this arsenic, whether in juices, nectars or waters, is present as As(III) and As(V). However, there is no European legislation for arsenic in fruit juice. Inconsistent results were obtained for arsenic between pooled and single samples. Also, the present work provided a clear example of how, due to a dilution factor, pooling might mask the presence of a contaminant and therefore underestimate exposure assessments. References [1] S. D. Conklin and P. E. Chen, “Quantification of four arsenic species in fruit juices by ion-chromatography–inductively coupled plasma–mass spectrometry,” Food Additives & Contaminants: Part A, vol. 29. pp. 1272–1279, 2012.